EFEK TERAPI BEKAM BASAH TERHADAP SKALA NYERI DAN KUALITAS HIDUP PADA PENDERITA NYERI KEPALA TENSION TYPE HEADACHE DI RUMAH BEKAM KOTA MEDAN TAHUN 2020 - TISYA SYARIE RIZKY PERDANA; HENDRA SUTYSNA (JURNAL ILMIAH MAKSITEK, 2021)
Headache is a neurological disorder with a variety of causes and is caused by primary and secondary disorders that cancause limitations in quality of life. Quality of life is an individual's perception of the cultural context and value system in whichthe individual lives and is related to the goals, expectations, standards and affairs they have. It provides the concept of anindividual's physical health, psychological condition, a person's beliefs, social relationships and a person's involvement withsomething important in their environment. Cupping therapy is a complementary and alternative therapy that is currentlydeveloping and can be used as a therapy for several pains, including headaches (including tension type headaches). Thisstudy aims to determine the effect of cupping therapy on pain scales and quality of life in people with tension typeheadache. This was a comparative analytic study conducted in an observational manner, using a prospective cohort studyapproach and observing the effects that occurred in one group without a comparison group by comparing the pre-post testbetween before and after the intervention. The research subjects were 13 people who were taken by consecutive samplingmethod. Data analysis using paired t test or Wilcoxon test. Wilcoxon test showed significant changes on the pain scale (p =0.001). In the domain of quality of life, the Wilcoxon test only found significant changes on the scale of physical function (p =0.001), vitality (p = 0.002), and pain (p = 0.001).Cupping therapy had a significant effect on pain scales, but not all quality oflife domains.